Dark energy in standard cosmology - Villegas, Fulgencio (2021)
A revision of the standard model of cosmology is presented with an emphasis on the Friedmann equation. A summary of the evidence for the accelerated expansion of the universe is shown; In order to explain such an acceleration in expansion, the characteristics of some dark energy models such as the cosmological constant, the quintessence, the K-essence and the Chaplygin gas are described and reviewed.